Allotransplantation of Freshly Isolated and Cryopreserved Mesenchymal Embryonic Cells, Stimulating the Rat’s Cartilage Reparative Regeneration - Revenko, E. B.; Babalyan, V. A.; Gorgol, N. I.; Volkova, N. A.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of freshly isolated and cryopreserved suspension of mesenchymal embryonic cells (MECs) on a reparative regeneration of rat’s cartilage defect at allogenic transplantation was under study. The MECs, procured by enzymatic and mechanical desaggregation of rat’s embryo tissue of 10-14 gestation day were selected as the initial material for comparative study of biological effect in the model of regenerating cartilaginous tissue. The viability of freshly isolated cell suspension made 94-96%, but for cryopreserved one that was no less than 50%. The collagen sponge, saturated with freshly isolated MECs suspension in one case, and cryopreserved one in another case, was applied for the cartilage defect plasty. It has been shown, that in the zone of cartilaginous defect at the allotransplantation of both freshly isolated and cryopreserved suspension of MECs, an intensive proceeding of biosynthetic and proliferative processes is observed, that results in a structural organisation and the young chondroid tissue formation. This fact permits to consider the transplantation as a perspective method for treating traumatic damages of articular cartilage.